2016
DOI: 10.1371/journal.pone.0146057
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Association between Adiposity Markers and Intraocular Pressure: The Kangbuk Samsung Health Study

Abstract: ImportanceIntraocular pressure (IOP) reduction or stabilization is the only proven method for glaucoma management. Identifying risk factors for IOP is crucial to understand the pathophysiology of glaucoma.ObjectiveTo examine the associations of change in body mass index (BMI), waist circumference, and percent fat mass with change in intraocular pressure (IOP) in a large sample of Korean adults.Design, setting and participantsCohort study of 274,064 young and middle age Korean adults with normal fundoscopic fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…4,5 Limited longitudinal studies have been conducted in East Asian populations, and these had furthermore presented conflicting results. 13 The Singapore Malay Eye Study reported a reduced IOP with normal aging in South East Asians. 11 In contrast, Nakano et al found a decrease in IOP over 10 years in a group of healthy Japanese male aircraft crew members.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…4,5 Limited longitudinal studies have been conducted in East Asian populations, and these had furthermore presented conflicting results. 13 The Singapore Malay Eye Study reported a reduced IOP with normal aging in South East Asians. 11 In contrast, Nakano et al found a decrease in IOP over 10 years in a group of healthy Japanese male aircraft crew members.…”
Section: Discussionmentioning
confidence: 99%
“…Association between sex and IOP had been reported with inconsistent results. 13 Further research is needed to better understand the mechanisms between gender and IOP association. 8,35 The Kangbuk Samsung Health Study found females had a lower IOP compared to males and the yearly decrease in IOP was also smaller in females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that Chang and colleagues use their Kangbuk Samsung Health Study to assess whether the decline in the estimated GFR might be associated more strongly with baseline lean mass rather than adipose tissue. As the authors recently reported (3), their healthy-worker cohort also provided measurements of bioelectric impedance and waist circumference. Thus, baseline values can be calculated for the percentage of fat and fat-free mass and the waist–height ratio.…”
Section: To the Editormentioning
confidence: 99%